Reconciliation of local and global symmetries for a class of crystals with defects - Parry, Gareth P.; Sigrist, Rachel (Springer, 2012)
We consider the symmetry of discrete and continuous crystal structures which are compatible with a given choice of dislocation density tensor. By introducing the notion of a 'defective point group' (determined by the dislocation density tensor), we generalize the notion of Ericksen–Pitteri neighborhoods to this context.